The First Data Release of CNIa0.02-A Complete Nearby (Redshift <0.02) Sample of Type Ia Supernova Light Curves* - Chen Ping; Dong Subo; Kochanek CS; Stanek KZ; Post RS; Stritzinger MD; Prieto JL; Filippenko Alexei V; Kollmeier Juna A; Elias-Rosa N; Katz Boaz; Tomasella Lina; et al. (IOP Publishing Ltd, 2022)
The CNIa0.02 project aims to collect a complete, nearby sample of Type Ia supernovae (SNe Ia) light curves, and the SNe are volume-limited with host-galaxy redshifts z (host) < 0.02. The main scientific goal is to infer the distributions of key properties (e.g., the luminosity function) of local SNe Ia in a complete and unbiased fashion in order to study SN explosion physics. We spectroscopically classify any SN candidate detected by the All-Sky Automated Survey for Supernovae (ASAS-SN) that reaches a peak brightness <16.5 mag. Since ASAS-SN scans the full sky and does not target specific galaxies, our target selection is effectively unbiased by host-galaxy properties. We perform multiband photometric observations starting from the time of discovery. In the first data release (DR1), we present the optical light curves obtained for 247 SNe from our project (including 148 SNe in the complete sample), and we derive parameters such as the peak fluxes, Delta m (15), and s (BV) .